2017
DOI: 10.15403/jgld.2014.1121.263.iac
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Use of 3 Direct-Acting Antiviral Regimen in a Large Cohort of Patients with Genotype-1b HCV Compensated Cirrhosis

Abstract: Background & Aims: Ombitasvir/Paritaprevir/ritonavir/Dasabuvir (OBV/PTV/r+DSV) is one of the elective direct-acting antivirals (DAAs) recommended by international guidelines and the only one covered by the National Insurance System in Romania until November 2016. Our aim was to present the first prospective Romanian cohort evaluating the effectiveness and safety in clinical practice of this 3DAA combination in patients with HCV genotype-1b Child A liver cirrhosis.Methods: 681 patients received OBV/PTV/r+DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
1
16
0
2
Order By: Relevance
“…The use of RBV was not associated with significant disutility, a fact that suggests a lower impact of side effects such as anaemia and pruritus, when administered in combination with DAA compared to when administered with interferon. This aspect reinforces the idea of the good tolerability of DAA in real life conditions [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…The use of RBV was not associated with significant disutility, a fact that suggests a lower impact of side effects such as anaemia and pruritus, when administered in combination with DAA compared to when administered with interferon. This aspect reinforces the idea of the good tolerability of DAA in real life conditions [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…Beyond clinical trials, numerous studies have evaluated the PTV/r/OBV + DSV combination administered for 12 weeks in clinical practice, all of them including a great proportion of patients with cirrhosis . As a whole, these studies have consistently shown SVR12 rates higher than 95% in all subgroups of patients, confirming data obtained from pivotal clinical trials.…”
Section: Introductionmentioning
confidence: 60%
“…Worldwide, one of the main causes of cirrhosis is the infection with hepatitis C virus (HCV) [2]. Direct acting antivirals (DAAs) introduced in 2014 have represented a revolution for the treatment of patients with HCV due to high sustained virologic response (SVR) rate (95-100% in genotype 1) and excellent tolerability [3,4]. Despite the proven SVR, there is still a risk of developing HCC that justifies careful monitoring of these patients [5].…”
Section: Introductionmentioning
confidence: 99%